Implementasi Nilai-Nilai Pancasila dalam Etika Komunikasi Antara Siswa dengan Guru di SMK Pemuda 1 Kesamben - Arum Widasari; Suhartono Suhartono; Cicik Pramesti (Universitas Palangka Raya, 2025)
The implementation of Pancasila values ​​in communication ethics between students and teachers is an important aspect in creating a harmonious and character-based educational environment. This study aims to describe how the implementation of Pancasila values ​​in communication ethics between students and teachers at SMK Pemuda 1 Kesamben. This study applies a qualitative descriptive approach with data collection techniques that include observation, interviews, and documentation studies. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions. To ensure the validity of the data, data triangulation techniques are used. The results of this study show that the implementation of Pancasila values ​​in student and teacher communication is reflected in three main indicators: (1) Politeness (the principles of Divinity and Humanity) can be seen from the choice of good and not rude words, the use of good language, and the right tone of voice. (2) Effectiveness of communication (the principle of Democracy) is shown through the delivery of clear and easy-to-understand opinions and maintaining communication on track. (3) Mutual respect (the principle of Unity and Social Justice) can be seen from respecting the teacher's opinion and respecting differences of opinion, listening when the teacher speaks, and responding wisely when communicating with the teacher. Class XI Accounting students at SMK Pemuda 1 Kesamben have implemented Pancasila values ​​in communication ethics with teachers during the PPKn learning well.